Equivalent-inclusion approach for estimating the elastic moduli of matrix composites with non-circular inclusions - Quyet, Tran Nguyen; Chinh, Pham Duc; Binh, Tran Anh (Vietnam Journal of Mechanics, 2015)
A novel approach to predict the effective elastic moduli of matrix composites made from non-circular inclusions embedded in a continuous matrix is proposed. In this approach, those inhomogeneities are substituted by simple equivalent circular-inclusions with modified elastic properties obtained from comparing the dilute solution results. Available simple approximations for the equivalent circular-inclusion medium then can be used to estimate the effective elastic moduli of the original composite. Robustness of proposed approach is demonstrated through the numerical examples with elliptic inclusions.